Moral enhancement and moral disagreement - Schaefer, GO (2014)
At first glance, the project of moral enhancement (making people more moral) may appear uncontroversial and obviously worth supporting; surely it is a good idea to make people better. However, as the recent literature on moral enhancement demonstrates, the situation is not so simple – there is significant disagreement over the content of moral norms as well as appropriate means by which to manipulate them. This disagreement seriously threatens many proposals to improve society via moral enhancement. In my dissertation, I develop an understanding of how, exactly, disagreement poses problems for moral enhancement. However, I also argue that there is a way forward. It is possible to bring about moral improvement without commitment to particular and controversial moral norms, but instead relying on relatively uncontroversial ideas concerning morally reliable processes. The upshot is that, while attempting to directly manipulate people’s moral ideas is objectionable, it is relatively unproblematic to focus on helping people reason better and avoid akrasia, with the justified expectation that this will generally lead to moral improvement. We should, therefore, focus not on how to bring people in line with what we take to be the right ideas, motives or behaviors. Rather, we should look to helping people determine for themselves what being moral consists in, as well as help ensure that they act on those judgments. Traditional, non-moral education, it turns out, is actually one of the best moral enhancers we have. In fact, the tools of philosophy (which is, in many aspects, concerned with proper reasoning) are central to the project of indirect moral enhancement. Ultimately, one of the best ways to make people morally better may well be to make them better philosophers.